Maududi’s discourse on Ilóh, Rabb, Dôn and Ñibódah - Haq, Md. Jahirul; Ushama, Thameem (IIUM Press, International Islamic University Malaysia, 2017)
Sayyid Abul Ala Maududi described the four key terms of the Qur’Én, i.e., IlÉh, Rabb, ÑIbÉdah and DÊn in his Qur’an Ki Char Bunyadi Istilahen in detail. He has shown that each of these terms does not bear only one meaning but rather they have other meanings too. To reach the comprehensive meaning of any of these particular terms, he suggested combining its all-probable meanings. However, many scholars criticise him for this interpretation. Thus, this study introduces this book; evaluates its features, its methodology of understanding and interpreting these four basic terms, and examines his approach of theological, philosophical and rational interpretations. Therefore, this book attempts to ascertain how far it is praiseworthy. This study adopts the approach of textual analysis in dealing with these four terms. The exploration depends basically on his book, Qur’an Ki Char Bunyadi Istilahen, his comments about these terms in his monumental tafsÊr, Tafhim al-Qur’an, and his other writings that discuss these terms. The authors found that whenever Maududi cautioned that the absence of true understanding might cause some people to commit some sorts of shirk unconsciously, he did not categorise or charge them as mushrikun. Likewise, whenever he categorised the state or the society as jÉhilÊ he meant that state or society has some characteristics of jÉhiliyyah. Throughout the discussion, Maududi used the methodologies propounded by previous scholars of this field, thus, his explanation is valid and it can be asserted that he has combined tafsÊr al-RiwÉyah with tafsÊr al-DirÉyah in explaining these terms. It can also be noted that Maududi emphasised much on Islamic state, where other acts of worship did not get enough importance.